2004
DOI: 10.1042/bj20031170
|View full text |Cite
|
Sign up to set email alerts
|

A single-fibre study of the relationship between MHC and TnC isoform composition in rat skeletal muscle

Abstract: In the present study, we investigated the possibility that MHC (myosin heavy chain) and TnC (troponin C) isoforms exist in specific combinations in rat-skeletal-muscle fibres. Single fibres (numbering 245) from soleus (predominantly slow-twitch) and sternomastoid (predominantly fast-twitch) muscles of adult rats were analysed for MHC and TnC isoform composition, using alanine-SDS/PAGE for separating MHC isoforms, and a novel method (based on the previously reported influence of Ca2+ on the mobility of Ca2+-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 28 publications
(34 reference statements)
2
45
0
Order By: Relevance
“…These fibres were denoted as mixed according to the classification of Bortolotto et al 5 and most probably contained both fast and slow isoforms of TnC and both type I and type II MHC. 5,15 In apparent accord with this, it can be seen in Table 1 …”
Section: Properties Of the Contractile Apparatussupporting
confidence: 83%
See 3 more Smart Citations
“…These fibres were denoted as mixed according to the classification of Bortolotto et al 5 and most probably contained both fast and slow isoforms of TnC and both type I and type II MHC. 5,15 In apparent accord with this, it can be seen in Table 1 …”
Section: Properties Of the Contractile Apparatussupporting
confidence: 83%
“…5 The Sr 2+ -activation characteristics of a fibre are determined by the type of TnC present (TnC-fast or TnCslow), but this, in fact, is always very closely related to MHC isoform composition of the fibre in non-transforming skeletal muscles of adult rat. 15 In a study of 241 single fibres from rat muscle, it was found that every fibre displaying simple Sr 2+ -activation characteristics was composed of at least 80%, and in most cases 100%, of one or other of the two broad classes of MHC, slow (type I) or fast (types IIA, IIX and IIB). Fibres in which the difference between the pCa 50 Fig.…”
Section: The Sr 2+ -And Ca 2+ -Activation Characteristics and Mhc Isomentioning
confidence: 98%
See 2 more Smart Citations
“…SDS-PAGE was performed on 7.5% resolving gels according to the method of O'Connell et al (21); the samples were thawed and vortexed thoroughly before being boiled for 5 min, and each well was loaded with 5 l of sample and 5 l of sample buffer. MHC markers consisting of single rabbit psoas and soleus fibers (muscles containing almost pure IIX and I isoforms, respectively) were then loaded in the end and middle lanes.…”
Section: Methodsmentioning
confidence: 99%